2019
DOI: 10.1111/1365-2656.12948
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal differences in baseline innate immune function are better explained by environment than annual cycle stage in a year‐round breeding tropical songbird

Abstract: Seasonal variation in innate immunity is often attributed to either temporal environmental variation or to life‐history trade‐offs that arise from specific annual cycle stages but decoupling them is difficult in natural populations.Here, we effectively decouple seasonal environmental variation from annual cycle stage effects by exploiting cross‐seasonal breeding and moult in the tropical Common Bulbul Pycnonotus barbatus. We test how annual cycle stage interacts with a key seasonal environmental variable, rain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 77 publications
4
20
0
Order By: Relevance
“…Instead they suggest flexibility within individuals to respond to local conditions. This result is consistent with findings from our earlier year-round study on Common Bulbuls in Jos where we found higher immune indices in the dry season compared to the wet season, and a further increase in some immune indices as the dry season progressed 43 . The high variability within locations (Table S1) confirms that innate immunity is highly flexible 26 .…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Instead they suggest flexibility within individuals to respond to local conditions. This result is consistent with findings from our earlier year-round study on Common Bulbuls in Jos where we found higher immune indices in the dry season compared to the wet season, and a further increase in some immune indices as the dry season progressed 43 . The high variability within locations (Table S1) confirms that innate immunity is highly flexible 26 .…”
Section: Discussionsupporting
confidence: 93%
“…This period coincides with the small breeding peak just before the onset of moult in the species 38 . In the same study, breeding Common Bulbuls had higher nitric oxide concentration, while moulting birds had lower concentrations, and this pattern was consistent within individuals 43 . Common Eiders Somateria mollissima also show higher nitric oxide concentration during breeding 80 .…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Note however, that diet composition affected haemagglutination titre during the first 12 weeks of the experiment (combined with ovotransferrin as PC1), thus the absence of a treatment effect in the full range of the experiment may be associated with increased variability in immune indices (Figure S3) observed after the onset of the rains (Figure S1). In the wild, innate immune function differs between the wet and dry season in common bulbuls (Nwaogu, Cresswell, Versteegh, & Tieleman, ; Nwaogu, ). The negative correlation between haptoglobin concentration and body mass may be due to a breakdown of muscle proteins to supply amino acids for hepatic acute phase protein synthesis (Jain et al, ; Londhe & Guttridge, ).…”
Section: Discussionmentioning
confidence: 99%